2016
DOI: 10.1017/s1355770x16000309
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of conservation agriculture on environmental efficiency among maize farmers in Zambia

Abstract: ABSTRACT. This paper explores the impact of conservation agriculture (CA) on the environmental efficiency of maize farmers in Zambia, by comparing nitrogen fertilizer recovery between farms that practise CA and those using conventional farming technologies. The Nitrogen Index Tier Zero tool is employed in generating a nitrogen balance sheet at the farm level. As CA technology may improve farmers' access to better technology, we employ a selectivity-corrected meta-frontier approach to account for potential sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 48 publications
3
42
0
1
Order By: Relevance
“…Generally, the Cobb-Douglas and the translog production frontiers are the commonly used functional forms in the production frontier literature. Several empirical studies have employed the translog frontier [25,[28][29][30][31][32], and have demonstrated that its estimates are better than those of the Cobb-Douglas. This study adopts the translog frontier after performing statistical tests on the significance of the squared and cross product terms of the explanatory variables.…”
Section: Empirical Model Specificationmentioning
confidence: 99%
“…Generally, the Cobb-Douglas and the translog production frontiers are the commonly used functional forms in the production frontier literature. Several empirical studies have employed the translog frontier [25,[28][29][30][31][32], and have demonstrated that its estimates are better than those of the Cobb-Douglas. This study adopts the translog frontier after performing statistical tests on the significance of the squared and cross product terms of the explanatory variables.…”
Section: Empirical Model Specificationmentioning
confidence: 99%
“…regressed on specific household socioeconomic characteristics, using the FRMs, following the example of recent studies (e.g., Abdulai and Abdulai, 2017;Ogundari, 2014;Ramalho, Ramalho, and Henriques, 2010). We report the specification of the test statistic for each of the FRMs 8 (logit, probit, loglog, and cloglog).…”
Section: Determinants Of Technical and Environmental Efficiencymentioning
confidence: 99%
“…A full description of the variables used in the analysis is presented in Table 1. The variables considered were selected based on a review of previous theoretical and empirical climate change related studies [10,15,36,[43][44][45][46][47][48]. The response variable is the expression of awareness of climate change and its risks to agriculture (alias climate change awareness), which equals 1 if the respondent replied "Yes" to the question: "Are you aware of climate change and its consequences on agriculture?…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%
“…Our hypotheses are that information sources positively affect climate change awareness among smallholder farm households, because it is through such sources that climate change information may be conveyed by relevant institutions. Following a review of literature on climate change [10,29,30,34,36,[45][46][47][48], our expectation is that the expression of climate change awareness and climate change adaptive measures have a positive relationship between them. Thus, as shown in Table 1, we considered a variety of adaptive factors that we hypothesize to affect expression of awareness of change among farmers.…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%